(untitled) (PLA Inside Out: An International Journal on Theory, Research and Practice in Prior Learning Assessment, 2026)
ePIC Conference Website: https://epic.openrecognition.org Open Recognition Alliance: https://openrecognition.org Documents supporting open recognition: • The Bologna Declaration on Open Recognition in 2016, a cheeky echo of the Bologna Accord, which gave rise to the Open Recognition Charter, adopted by the government of Normandy • The Paris Declaration on the Equality of Recognitions in 2024 • The Open Recognition Manifesto in 2025, covered in this issue of PLAIO